Strategi Kepala Madrasah dalam Meningkatkan Nilai Tambah Pendidikan Era Society 5.0 (Studi Kasus MAN Insan Cendekia Serpong) - Nikma, Sulalatun; Asy'ari, Hasyim; Ratnaningsih, Sita (STAI Auliaurrasyidin Tembilahan, 2023)
Education in the era of society 5.0 requires students to have significant added value, this problem indirectly requires teachers to have teaching skills with a digitalization system. This research method is qualitative-descriptive with a case study type. The results of the research show that the planning and implementation of added value in education in the era of Society 5.0 is through: 1) Decentralizing education through a performance-based PPDB system in all regions of Indonesia. 2) Reducing bipolarization through MASTAMA and Olympic and event-based career management. 3) Democratic education through the integration of science and technology and imtak curricula as well as madrasah services in the form of workshops and outreach. 4) Community participation through madrasa committees. 5) Agent of change through the use of laptops, strong social attitudes and religiosity, e-learning systems and LMS, and homestay programs. The value-added model is increasing, as shown by the UTBK results in 2021 and 2022. The number of students entering PTN through the UTBK-SNBT route in 2023 was 89 students out of 114 students or 78%, and students entering through the SNBP achievement route was 22 students out of 56 students or 39.09%. The obstacle faced by the teachers is the lack of communication between the school teachers and the dormitory teachers, which has an impact on program delays that require coordination between the parties involved. The solution is for the madrasa director to open a line of communication between the school and the dormitory so that it can work well and smoothly.